ANTESEDEN KETERIKATAN PROGRAM STUDI ILMU-ILMU SOSIAL PTS DI YOGYAKARTA BERBASIS TEORI PERTUKARAN SOSIAL - Danang Sunyoto; Yanuar Saksono (Jurnal Inovasi Penelitian, 2022)
Objectives-This study aims to examine and examine the effect of perceived organizational support and distributive justice on the engagement of social science study programs at private universities in Yogyakarta based on Social Exchange Theory. Population/Object/Research Model-The population of this research is 113 social science study programs in private universities in Yogyakarta and 105 study programs meet the requirements as data. While the object of group research consists of the chairperson and secretary of the department. The research model uses the census model. The independent variables include perceptions of organizational support and distributive justice, as well as the dependent variable, namely group attachment. Findings-The results show that the high or low engagement of the social sciences study program of private universities in Yogyakarta is not influenced by perceptions of organizational support, but is influenced by distributive justice. Originality-There are still opportunities for studies on the engagement of social science study programs at private universities in Yogyakarta, both as mediators and predictors using group data objects.